Characteristics and the formation mechanism of the dolomite reservoirs for Lower Ordovician Majiagou Formation, central Ordos Basin, China - Tian, Kun; Zhou, Jinsong; Yin, Xiao; Xue, Chunqi; Cao, Jun; Ma, Ling; Zhao, Weibo (Frontiers in Earth Science, 2025)
The distribution of anhydrite contributes to the formation of high-quality dolomite reservoirs. However, the lower part of the Lower Ordovician Majiagou Formation in the central Ordos Basin shows significant natural gas potential despite in anhydrite-depleted settings. Therefore, its formation mechanism is crucial for carbonate hydrocarbon exploration in evaporite-depleted regions globally. Through integrated multidisciplinary analysis (petrography, cathodoluminescence (CL), X-ray diffraction (XRD) and carbon (C)-oxygen (O)-strontium (Sr) isotopes), the sedimentary-diagenetic differentiation mechanism of dolomite reservoirs in the study area was revealed. Two types of dolomite mainly develop in the study area. (Very) finely dolomite (Md1) is composed by micritic or microcrystalline (<20 μm), euhedral to subhedral dolomite crystals with laminated structure observed, the CL shows a very dull or dark red in color, low order degree (0.65 on average), a positive δ13C shift (+0.83‰ on average), high Sr isotope ratio (87Sr/86Sr = 0.70967 on average) and paleosalinity Z value (125.9747 on average). Fine-medium crystalline dolomite (Md2) is composed by finely or medium crystalline (20-60 μm), euhedral to subhedral dolomite crystals, the dark red or orange in color by CL analysis, high order degree (0.85 on average), a negative δ18O shift (−7.12‰ on average), low Sr isotope ratio (87Sr/86Sr = 0.70946 on average) and paleosalinity Z value (122.8781 on average). It is indicated that Md1 formed in a restricted platform tidal flat environment with weak hydrodynamic conditions, during the syngenetic-quasi syngenetic stages through the seepage reflux of high-salinity seawater in an open, low-oxidation, low-temperature environment. Md2 formed through the superimposed transformation of the original tidal flat shoal during the shallow burial stage, driven by the reflux of reducing seawater in a closed, low-reduction, higher-temperature environment. In addition, the atmospheric freshwater dissolution and the enhanced euhedral growth of dolomite crystals during the burial stage promote the development of high-quality reservoirs. This study provides novel geochemical and sedimentary insights for predicting dolomite reservoirs in anhydrite-depleted settings, aiding global hydrocarbon exploration in similar basins.